2010
DOI: 10.1055/s-0030-1249810
|View full text |Cite
|
Sign up to set email alerts
|

The Intestinal Permeability of Neolignans from the Seeds ofMyristica fragransin the Caco-2 Cell Monolayer Model

Abstract: The intestinal permeability and transport of 10 neolignans isolated from MYRISTICA FRAGRANS were studied by using the Caco-2 cell monolayer model. The 10 neolignans were measured by HPLC. Transport parameters and permeability coefficients were then calculated and compared with those of the model compounds, propranolol and atenolol. Among the 10 neolignans, the 8- O-4'-type neolignans demonstrated high permeability while the benzofuran-type neolignans were of poor to moderate permeability. Among them, eight neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 28 publications
(35 reference statements)
0
20
0
Order By: Relevance
“…All metabolites were isolated and identified by a combination of solvent extraction, chromatographic and spectroscopic methods. The third study, investigated gastrointestinal absorption of ten neolignans, including licarin A, methoxylicarin A, licarin B, myrislignan and others in the Caco-2 cell permeability assay (Yang et al 2010). The study showed that transport of the 8,4’-oxyneolignans, such as myrislignan, across Caco-2 monolayers was superior to that of the benzofuranoid-type licarins.…”
Section: Analysis Of Major Constituents Of Nutmegmentioning
confidence: 99%
“…All metabolites were isolated and identified by a combination of solvent extraction, chromatographic and spectroscopic methods. The third study, investigated gastrointestinal absorption of ten neolignans, including licarin A, methoxylicarin A, licarin B, myrislignan and others in the Caco-2 cell permeability assay (Yang et al 2010). The study showed that transport of the 8,4’-oxyneolignans, such as myrislignan, across Caco-2 monolayers was superior to that of the benzofuranoid-type licarins.…”
Section: Analysis Of Major Constituents Of Nutmegmentioning
confidence: 99%
“…In the Caco-2 cell monolayer model, permeability was described by P AB values (the apparent permeability coefficients from AP to BL side). The P AB values of well-transported and poorly transported compounds were > 1 × 10 −5 and < 1 × 10 −6  cm/s, respectively [16, 17]. P AB values of the marker compounds propranolol (3.81 ± 0.34 × 10 −5  cm/s) and atenolol (7.76 ± 4.65 × 10 −7  cm/s) in our experiments were consistent with previous reports (Table S5).…”
Section: Resultsmentioning
confidence: 99%
“…Reference compounds propranolol and atenolol were used to validate the Caco-2 cell monolayer model. They represent paracellular flux and transcellular flux compounds, respectively [16, 17]. Differentiation of Caco-2 cells was checked on days 8, 15, 21 by determining the alkaline phosphatase activity using the AKP assay kit, a brush border enzyme marker [15, 25].…”
Section: General Experimental Proceduresmentioning
confidence: 99%
“…We have investigated the intestinal permeability and transport of MRL and other neolignans from the nutmeg using the human Caco-2 cell monolayer model. The results indicated that MRL exhibits higher permeability in Caco-2 cell model than cyclic neolignan, such as dehydrodiisoeugenol [20]. The study in vitro also indicated that MRL can be transformed into seven metabolites by liver microsomes, CYP450s [21].…”
Section: Introductionmentioning
confidence: 90%